Effects of Exergaming on Morphological Variables, Biochemical Parameters, and Blood Pressure in Children and Adolescents with Overweight/Obesity: A Systematic Review with Meta-Analysis of Randomized Controlled Trials - Herrera-Valenzuela, T; Cid-Calfucura, I (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Objectives: This systematic review with meta-analysis aimed to evaluate the available body of published peer-reviewed studies on the effects of exergaming (EXG) compared to the control group (CG) on morphological variables, biochemical parameters, and blood pressure in children and adolescents with overweight/obesity. Methods: A systematic literature search was conducted until September 2024 using five databases: PubMed, Medline, CINAHL Complete, Scopus, and Web of Science. PRISMA, TESTEX, RoB 2, and GRADE tools assessed the methodological quality and certainty of evidence. Hedge’s g effect sizes (ES) for morphological, biochemical, and blood pressure variables were calculated for meta-analyses. Using a random effects model, potential sources of heterogeneity were selected, including subgroup analyses (age) and single training factor analysis (program duration, training frequency). The protocol was registered in PROSPERO (code: CRD42024626992). Results: Out of 72 records, 6 randomized controlled trials with 191 children and adolescents with overweight/obesity were included. Nine meta-analyses were performed, showing significant decreases in body mass index (p = 0.04), waist circumference (p = 0.03), and systolic blood pressure (p = 0.007). However, no significant improvements were observed in diastolic blood pressure, body fat percentage, total cholesterol, HDL-cholesterol, LDL-cholesterol, triglycerides, and glucose. Subgroup analyses showed significant decreases in total cholesterol (<15 years, ES = 0.56; p = 0.006), HDL-cholesterol (<15 years, ES = 0.51; p = 0.01), LDL-cholesterol (<15 years, ES = 0.63; p = 0.01), and triglycerides (<15 years, ES = 0.82; p = 0.000). In training duration, only significant decreases in total cholesterol (ES = 0.69; p = 0.02) were presented in favor of <12 weeks vs. ≥12 weeks. While in training frequency only significant decreases in triglycerides (ES = 0.70; p = 0.03) were reported in favor of ≥3 sessions per week vs. <3 sessions per week. Conclusions: EXG significantly decreases body mass index, waist circumference, and systolic blood pressure in children and adolescents with overweight/obesity. © 2024 by the authors.